1999
DOI: 10.1007/s002340050713
|View full text |Cite
|
Sign up to set email alerts
|

Primary nerve-sheath tumours of the trigeminal nerve: clinical and MRI findings

Abstract: We reviewed the clinical and MRI findings in primary nerve-sheath tumours of the trigeminal nerve. We retrospectively reviewed the medical records, imaging and histological specimens of 10 patients with 11 primary tumours of the trigeminal nerve. We assessed whether tumour site, size, morphology or signal characteristics were related to symptoms and signs or histological findings. Histological proof was available for 8 of 11 tumours: six schwannomas and two plexiform neurofibromas. The other three tumours were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…Majoie et al [26] and Rigamonti et al [27] described dumb-bells configuration of trigeminal schwannomas due to involvement of CPA and Meckel's cave. In one patient in the present study, the trigeminal schwannoma extended through the foramen ovale as was reported by Kapila et al [28].…”
Section: Discussionmentioning
confidence: 99%
“…Majoie et al [26] and Rigamonti et al [27] described dumb-bells configuration of trigeminal schwannomas due to involvement of CPA and Meckel's cave. In one patient in the present study, the trigeminal schwannoma extended through the foramen ovale as was reported by Kapila et al [28].…”
Section: Discussionmentioning
confidence: 99%
“…Plexiform neurofibroma (PNF) may occur at any age and is typically found in about one-third of patients with neurofibromatosis type 1 (NF-1). 1 PNF most commonly involves the trigeminal nerve, especially its 1st and 2nd divisions. Primary nerve sheath tumours of the trigeminal nerve may occur with a wide variety of symptoms and signs, including trigeminal sensory deficit, atypical neuralgia or paraesthesia, absent corneal reflex and diplopia, depending on lesion location.…”
Section: Introductionmentioning
confidence: 99%
“…A diffuse neurofibroma involving the skin and subcutaneous tissues is a common variant of neurofibroma which is often seen in head and neck region and may involve the oral cavity [15]. In the head and neck, plexiform neurofibromas most commonly involve the fifth cranial nerve, especially the first and second divisions [16].…”
Section: Introductionmentioning
confidence: 99%